PENERAPAN KOMUNIKASI DEMOKRATIS DAN KONSTRUKTIF DALAM PENYELESAIAN SENGKETA PERTANAHAN - Loso Judijanto; Al-Amin (ADISAM PUBLISHER, 2025)
Land dispute resolution in Indonesia often faces complex challenges due to conflicting interests, lack of transparency, and weak communication between parties. The implementation of democratic and constructive communication is a strategic solution to overcome these problems. Through this approach, all parties involved are given equal space to express their opinions, supported by data transparency and facilitation by neutral parties such as the National Land Agency (BPN). Open deliberation, mediation, and socialisation processes can create a healthy dialogue, strengthen trust, and produce fair and mutually acceptable decisions. Thus, democratic and constructive communication has proven eflective in achieving sustainable and equitable resolution of land disputes